Effect of dental pigmentation intensity on the transenamel and transdentinal penetration of hydrogen peroxide - Moreira, Janaina Cardoso [UNESP]; Gallinari, Marjorie de Oliveira [UNESP]; Rahal, Vanessa [UNESP]; Fagundes, Ticiane Cestari [UNESP]; dos Santos, Paulo Henrique [UNESP]; de Moura, Marcia Regina [UNESP]; Briso, André Luiz Fraga [UNESP] (FapUNIFESP (SciELO), 2016)
This study aimed to evaluate the transenamel and transdentinal penetration of hydrogen peroxide (H202) applied to bovine teeth pigmented with black tea at different intensities. The following groups were formed DW: immersion in distilled water; BT100: immersion in an infusion of 1.6 g of black tea per 100 mL distilled water; BT10: immersion in an infusion of 1.6 g black tea per 10 mL distilled water. All groups were immersed for 6 days. To quantify the penetration of H202, the specimens were placed in artificial pulp chambers (APCs) and subjected to bleaching treatment with 38% H2O2 once per week for 3 weeks. After bleaching treatment, the acetate buffer solution of APCs with peroxidase enzyme was evaluated in a reflection spectrophotometer. The transenamel and transdentinal penetration of H2O2 and the L* values obtained at T1, T2 and T3 were subjected to Kruskal-Wallis and Friedman statistical tests. At T1, the H2O2 diffusion in DW was higher than that in BT100 and BT10. At the other evaluation times, the penetration values in BT100 and BT10 increased and remained similar. The L* values increased significantly in all groups at T1. At T2, the L* values were higher in DW, while the values in BT100 and BT10 were similar to each other. At the end of the experiment, BT10 showed the lowest L* values. The pigmentation level did not affect the penetration of H2O2 through the enamel and dentin and the bleaching agent effectively changed the color of the teeth.
Keywords: Dental bleaching; Hydrogen peroxide; Pigmentation